Natural antioxidant contents in the seeds of four roselle Malaysian varieties and a kenaf: a comparison - Darnis, Deny Susanti; Osman, Mohamad; Draman, Nurul Nadiah (Taylor & Francis Group, 2012)
The natural antioxidant contents in the ethanol extract of the seeds of four varieties of Roselle (UKMR-1, UKMR-2, UKMR-3, and UMKL-1) and Kenaf (V36) were evaluated. The ground seeds were extracted in ethanol by a Soxhlet apparatus. The results indicated that the highest seeds’ extract yield was V36 (27%), followed by UKMR-2 (21%), UMKL-1 (20%), UKMR-3 (15%), and UKMR-1 (14%). The total phenolic and flavonoid content in extracts were determined by Folin-Ciocalteu and aluminium chloride assays, respectively. The V36 had higher TPC and TFC than the Roselle varieties tested. However, there was no difference among the Roselle varieties studied in their TPC and TFC.